KNOWLEDGE AND AWARENESS OF PREGNANT FEMALES REGARDING ANTENATAL PHYSICAL THERAPY IN TERTIARY CARE HOSPITALS OF PESHAWAR; A DESCRIPTIVE CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
Background: Physical therapy includes different exercises that keep patients physically and mentally fit. During pregnancy, a woman's body goes through a lot of changes, both physically and mentally. It's especially helpful for pregnant females during and after pregnancy. Antenatal physical therapy, which is recommended by the World Health Organization (WHO), is a big part of this care. It helps prevent muscle and joint pain and provides group therapy for mental and physical health. It also helps avoid other problems like bladder issues, back pain, fatigue, and high blood pressure. Despite its benefit, there is a little knowledge and awareness about antenatal physical therapy among pregnant females. Objective: To determine the knowledge and awareness of pregnant females regarding antenatal physical therapy in tertiary care hospitals of Peshawar. Methodology: A descriptive cross-sectional study was conducted in five hospitals in Peshawar (four government and one private). A total of 377 pregnant females in any trimester with an age range of 18- 45years were approached and interviewed through a pre-examined questionnaire. Descriptive analysis was done using SPSS version 25. Results: In this survey 377 of the total population of pregnant women of age from 18-45 years were taken. The mean age of participants was 24.66 ±4.794. The education level of participants was that: 34.22% has never attended school, 28.36% has completed their secondary education and only 5.84% has done bachelor or above. Among 377 participants n=32(8.49%) has knowledge about the physical therapy service during pregnancy and n=345(91.51%) do not have any idea about it. Conclusion: This study shows that the knowledge and awareness of pregnant females regarding antenatal physical therapy was very low. There is a crucial need to educate pregnant females about the use of antenatal physical therapy during pregnancy through surveys and workshops.